Pendidikan Kesehatan Tentang Pencegahan Penularan Covid-19 Bagi Siswa Sekolah Dasar - Taty Hernawaty; Arlette Puspa Pertiwi; Wiwi Mardiyah; Hadi Suprapto Arifin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
During the Covid-19 pandemic, the government set various policies to prevent transmission. The use of masks, practicing a clean and healthy lifestyle, and limiting distance and even Large-Scale Social Restrictions are the efforts that have been set. However, many violations are still being committed, including school children who have had face-to-face meetings (PTM) at school. Disobedience to implementing health protocols can be caused by a lack of knowledge. This health education activity is about preventing the spread of Covid-19. Activities are carried out offline when students do PTM at Bojong 01 Elementary School, Majalaya District, Bandung Regency, totaling 44 students. The results of this activity showed that there was an increase in students' knowledge about preventing the transmission of Covid-19 by 5.45% from previous knowledge so that it became 88.18%. Good knowledge about preventing the transmission of Covid-19 can be a strengthening basis for the formation of a healthy lifestyle. In conclusion, students' knowledge about preventing the transmission of Covid-19 increased after being given health education. Suggestions, the next study is an effort to increase students' positive attitudes so that they can form good behavior in preventing the transmission of Covid-19.